Does Productivity Differ in Domestic and Foreign Firms? Evidence from the Indian Machinery Industry - Chandan Sharma (Indian Economic Review, 2010)
This study aims to evaluate the productivity performance of foreign and domestic firms of the machinery industry in India. Using information of more than 200 firms of three sub-industries namely electrical, electronics and non-electrical, we compare both types of firms total factor productivity (TFP) for the period of 1994-2006. At the first stage, our empirical analysis utilizes a non-parametric approach based on the principle of first order stochastic dominance. Comparing the distributions of the measures of firms performance across the groups, we find that the distributions for foreign firms dominate that of domestically owned Indian firms in two industries. In the next stage, the study estimates determinants of productivity growth of firms. The results of our analysis suggest that in the electrical industry foreign ownership matters, however, in other two industries there is no significant difference between both types of firms. The results also reveal that those firms which import and have in-house R&D facilities are more productive. Finally, the role of public infrastructure is found to be vital in the firms productivity growth for the sample of industries considered.